Literature Review : The Role of Forensic Audit, Investigative Audit, Auditor Competence, Spiritual Intelligence and Information Technology on Fraud Detection - Abel Desiyanti Manik; Elisa Cici Prisilia; Juana Dewi Maharani; Handriyani Dwilita (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the role of forensic audit, investigative audit, auditor competence, spiritual intelligence, and information technology in detecting fraud. Using a qualitative method with a literature review, the results showed that forensic auditing is effective in detecting and proving fraud through investigative techniques, while investigative auditing focuses on identifying modus operandi and collecting evidence. Auditor competence, which includes technical expertise, accounting, and legal understanding, is critical to uncovering fraud. Spiritual intelligence helps auditors maintain integrity, while information technology supports fraud detection through data management systems and audit software. Synergy between all these factors is necessary to improve fraud detection and prevent further losses to the company. This research is expected to contribute to the development of more effective audit methods to reduce the risk of fraud.